Determining the Application of Small Extracellular Vesicles (SEVs) as Biomarkers of Arsenic Induced Urothelial Injury and Carcinogenesis - Washuck, Nicole (Université d'Ottawa / University of Ottawa, 2022)
Arsenic is a toxic metalloid that continues to contaminate the water and food sources of millions of people globally. Among the numerous health effects of arsenic exposure are urothelial toxicity and cancer. In recent years, small extracellular vesicles (SEVs) have been shown to be vital in intracellular communication and have been used in clinical studies as biomarkers of disease. The overall goal of this thesis is to understand the mechanisms of cell communication during arsenic exposure and to develop minimally invasive biomarkers for the toxic responses. The specific objectives are to: a) determine if SEVs released from arsenic exposed urothelial cells are responsible for mediating urothelial toxicity; and b) assess the application of urinary SEVs as novel biomarkers of arsenic exposure in an exposed population. The hypothesis leading this research is that the biology and protein packaging profile of urothelial SEVs are altered following arsenic exposure because of the induction of cell stress signaling pathways. I also hypothesize that urinary SEV proteins can be used as biomarkers of arsenic exposure because they are positively correlated with urinary arsenic concentrations in an exposed population. SVHUC1 human urothelial cells were dosed with sodium meta arsenite (1, 2, and 5 uM) for 48 hours. T24 urothelial carcinoma cells were also grown in parallel to compare for carcinogenicity. A label-free quantitative proteomics approach was used to assess the differentially expressed proteins in the cell lysate and the SEVs extracted from the culture media to determine the mechanistic pathways involved and how well the protein profiles in SEVs correlate with those in the cell lysate. SEVs were isolated from the archived urine samples of participants (n=36) enrolled in the Yellow Knife Health Effects Monitoring Program (YKHEMP) and two potential biomarkers, transforming growth factor beta receptor 1 (TGFBR1) and ribonuclease inhibitor 1 (RNH1), were measured by an enzyme linked immunosorbent assay (ELISA). SEVs in all samples were successfully characterized based on their size (50-200 nm) and positive antibody array for eight protein markers indicating their endosomal biogenesis. The total number of SEVs was not shown to increase following arsenic exposure in the in vitro study. However, the cancerous T24 cells had nearly four times higher numbers of SEVS compared to the non-cancerous SVHUC1 cells. The changes in the protein profiles in SEVs released following arsenic dosage indicated activation of pathways important for cell survival, viability, and migration and inactivation of pathways related to cell death and necrosis which were also observed in the paired cell lysate samples. Comparison between paired SEV and cell lysate samples, however, indicated selective SEV packaging of proteins which may be for the purpose of intracellular communication. Comparative assessment of SEVs from T24 and arsenic exposed SVHUC1 cells showed similar activation of cancer related pathways including those responsible for malignant tumors and increased proliferation rates. From the in vitro study results, we identified 8 potential SEV biomarkers. Of which, TGFBR1 showed the most promising association, having been positively associated with both inorganic arsenic and cadmium concentrations in urine samples. This thesis showed that SEVs are important mediators of arsenic exposure in urothelial cells and highlighted the comparability of SEV and cell lysate analysis. Furthermore, TGFBR1 was identified as a promising biomarker of arsenic exposure for its positive association with increased arsenic both in vitro and in human biomonitoring analysis.
Keywords: Biomarkers; Arsenic; Toxicology; Bladder Cancer; SEVs; Extracellular vesicles